Letter from Georg Bredig to Max Bredig, October 4, 1937 - Bredig, Georg (1937)
In a letter to his son, Max Bredig (1902-1977), who has recently arrived in the U.S.A., Georg Bredig (1868-1944) expresses his joy in receiving a letter from Max and the confirmation of his safe journey overseas. Georg also offers Max personal advice, including balancing self-confidence with modesty and avoiding complications by refraining from objections to his dismissal or the leave conditions of the Bavarian Nitrogen Works. Georg concludes the letter by confirming the arrival of Max's family documents in Berlin, asking Max to take care of himself in his new homeland, and wishing him well in his new endeavors.
Keywords: Jews, German; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Emigration and immigration